Psychological Views of Ibn-Aljawzi (Journal of the College of Education for Women, 2018)
The researcher found that neglecting our Arab Islamic heritage and bragging about what the West came in the field of education and psychology is common in our curriculumSo the researcher found it necessary to identify the thought of our media Arab Muslims like Ibn Al-Jawzi being a remarkable figure in the world of human thought therefore, the researcher in this research decided to identify his educational and psychological ideas and psychological emotions in his mind and methods of control and characteristics of the human soul and methods of development of the Muslim character by following the descriptive analytical approach.